Emerging Roles of Heat-Induced circRNAs Related to Lactogenesis in Lactating Sows - Sun, Jiajie; Zhang, Haojie; Hu, Baoyu; Xie, Yueqin; Wang, Dongyang; Zhang, Jinzhi; Chen, Ting; Luo, Junyi; Wang, Songbo; Jiang, Qinyan; Xi, Qianyun; Chen, Zujing; et al. (Frontiers in Genetics, 2020)
Heat stress negatively influences milk production and disrupts normal physiological activity of lactating sows, but the precious mechanisms by which hyperthermia adversely affects milk synthesis in sows still remain for further study. Circular RNAs are a novel class of non-coding RNAs with regulatory functions in various physiological and pathological processes. The expression profiles and functions of circRNAs of sows in lactogenesis remain largely unknown. In the present study, long-term heat stress resulted in a greater concentration of serum HSP70, LDH, and IgG, as well as decreased levels of COR, SOD and PRL. Heat stress reduced the total solids, fat, and lactose of sow milk, and heat stress significantly depressed CSNαs1, CSNαs2 and CSNκ biosynthesis. Transcriptome sequencing of lactating porcine mammary glands identified 42 upregulated and 25 downregulated transcripts in heat stress vs. control. Functional annotation of these differentially-expressed transcripts revealed 4 heat-induced genes involved in lactation. Moreover, 29 upregulated and 21 downregulated circRNA candidates were found in response to heat stress. 42 positively correlated circRNA-mRNA expression patterns were constructed between the 4 lactogenic genes and differentially expressed circRNAs. Five circRNA-miRNA-mRNA post-transcriptional networks were identified involving genes in the heat stress response of lactating sows. In this study we establish a valuable resource for circRNA biology in sow lactation. Analysis of a circRNA-miRNA-mRNA network further uncovered a novel layer of post-transcriptional regulation that could be used to improve sow milk production.